2009
DOI: 10.3109/00207450903149217
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Toxoplasma Gondii Infection in Diseases Presenting With Headaches. Headaches and Aseptic Meningitis May Be Manifestations of the Jarisch-Herxheimer Reaction

Abstract: Worldwide, approximately 2 billion people are chronically infected with T. gondii with largely unknown consequences. This review presents clinical symptoms, differential diagnosis, triggering factors, treatment, and pathomechanisms responsible for idiopathic intracranial hypertension, pseudotumor cerebri, and aseptic meningitis. Literature cited in this work illustrates that immune state and other biologic mediator imbalances due to various endogenous and exogenous triggering factors may markedly affect latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 158 publications
(183 reference statements)
0
24
1
Order By: Relevance
“…Substantial evidence has established an association between T. gondii infection and headaches (44) ; however, in our study, no association was observed. Ocular disease has also been reported to be linked with T. gondii infection, particularly in the U.S. (45) .…”
Section: Discussioncontrasting
confidence: 56%
“…Substantial evidence has established an association between T. gondii infection and headaches (44) ; however, in our study, no association was observed. Ocular disease has also been reported to be linked with T. gondii infection, particularly in the U.S. (45) .…”
Section: Discussioncontrasting
confidence: 56%
“…In vitro studies that mimic an immunocompromised state have shown that the conversion occurs within 1 week regardless of the age of the brain cysts (5). In immunocompetent hosts, the presence of cysts caused by T. gondii (referred to here as "T. gondii cysts") in the brain seems to be associated with various neurological disorders (27), including cryptogenic epilepsy (37), migraine (25), schizophrenia (38), Malloret meningitis (26), and affective (36) and behavioral (11) disorders.…”
mentioning
confidence: 99%
“…Also, within a headache clinic population Tietjen et al [814] identified diabetes mellitus as a migraine comorbidity constellation. However, in a large population-based cross-sectional study performed in Norway, Aamodt et al [810] found the inverse relationship between migraine and diabetes. Prevalence odds ratios of migraine was lower amongst persons with diabetes compared with those without diabetes, the OR being 0.4 (95% CI: 0.2-0.9) for T1DM, and 0.7 (CI: 0.5-0.9) for T2DM.…”
Section: Possible Association Between Diabetes Migraine/other Type Omentioning
confidence: 97%
“…The prevalence of migraine and tension-type headache in the patients with diabetes mellitus was found to be higher as compared with controls without diabetes [810][811][812]. The disease was more common amongst teenagers with migraine compared with those without migraine [813].…”
Section: Possible Association Between Diabetes Migraine/other Type Omentioning
confidence: 99%